From the mountain of Yhwh to Israel's mnuḥh the desert itinerary of Numbers 10:11-36 - Leder, Arie C. (Old Testament essays, 2016)
This essay argues that the post-Sinai itinerary narratives depicted in Numbers are organized into two clusters (Num 10:11-36 and 20:2222:1), both of which depict the first generation of Israelites of the exodus, and that the first of these functions as the conclusion to Num 1:1-10:10. The first narrative depicts a generation fully instructed and compliant with divine instruction (Num 1:1-10:10) that resumes the march that began on Passover night, upon the Lord's command given through Moses (10:13). The goal of the first itinerary cluster is the ark finding rest for the people (מנוחה, Num 10:33). Furthermore, this essay argues that the syntactical function of the itinerary verbs in Num 11:35 and 12:16 subordinate them to the theme of complaint and rebellion against authority, which begins in 11:1, and that therefore they do not depict the continuation of the journey that began in Num 10:12. It is within this narrative of complaint that the second itinerary cluster emerges, beginning in Num 20:22 and ending in 22:1, to depict the same generation as non-compliant and rebellious.